CCL3L1 and CCR5 influence cell-mediated immunity and affect HIV-AIDS pathogenesis via viral entry-independent mechanisms (2007)
Although host defense against human immunodeficiency virus 1 (HIV-1) relies mainly on cell-mediated immunity (CMI), the determinants of CMI in humans are poorly understood. Here we demonstrate that variations in the genes encoding the chemokine CCL3L1 and HIV coreceptor CCR5 influence CMI in both healthy and HIV-infected individuals. CCL3L1-CCR5 genotypes associated with altered CMI in healthy subjects were similar to those that influence the risk of HIV transmission, viral burden and disease progression. However, CCL3L1-CCR5 genotypes also modify HIV clinical course independently of their effects on viral load and CMI. These results identify CCL3L1 and CCR5 as major determinants of CMI and demonstrate that these host factors influence HIV pathogenesis through their effects on both CMI and other viral entry-independent mechanisms.